Crediting worker education? Insights from South African experiences. (2nd September 2021) - Allais, Stephanie
ABSTRACT: This paper explores South African experiences in using formal credentials in worker education. In specific, it analyses the value and use of the outcomes-based, unit standards-based qualifications registered on the South African national qualifications framework for "trade union practice." Creating formal qualifications for worker education programmes was hotly debated for many years in the labour movement. The paper finds little evidence of positive achievement of the creation of a formal qualification route for trade unionists. The main stated reason for the introduction of the formal qualification route was to support the educational and labour market mobility of union activists. There is no evidence of this to date, and the paper argues that the design of the qualification makes it unlikely to become a possibility. The existence of the qualification has facilitated funding for worker education, but a greater success would have been to convince public bodies to fund worker education according to its intrinsic logic. The paper also finds that to date the negative consequences that many unionists predicted in these debates have not arisen. However, this seems to be in spite of and not because of the qualification model and may be attributable to the strength of the single provider of the qualification.